SAFETY RIDING, BENTUK PELAKSANAAN PELATIHAN PADA PT SARANA AMAN BERKENDARA JAKARTA SELATAN - Nurul Giswi Karomah; Nur Ainun (POLITEKNIK LP3I JAKARTA, 2020)
This study aims to find out how the form of conducting safety riding training at PT Sarana Aman Berkendara, find out the constraints faced and find out the solutions made in overcoming the obstacles faced.The form of implementation and training in safety rite consists of 3 (three) stages, namely; pre test, theory & practice material, Post test. In the implementation of safety riding training there are several obstacles, namely Lack of order among the trainees so that it is not in accordance with the time provided, Lack of preparation of training participants' data, Limited office facilities, Weather that often changes, Number of participants. Solutions in dealing with obstacles in the implementation of safety riding training that is Handling obstacles in the lack of order of the trainees, Handling obstacles in the lack of preparation of participants' training data, Handling constraints in limited office facilities, Handling constraints on the weather that often changes, Handling constraints in the number of participants. This research is descriptive qualitative, with observation, interview and documentation techniques.Keywords: Safety Riding, Implementation, Training